SOSIALISASI KEBIJAKAN DAN STRATEGI SEKOLAH RAMAH ANAK BAGI MAHASISWA PGSD UNIVERSITAS MATARAM - Siti Istiningsih; Dyah Indraswati; Aisa Nikmah Rahmatih; Asri Fauzi; Muhammad Sobri; Deni Sutisna (Jurnal Warta Desa (JWD), 2021)
Cases of violence against children are still common in school environments, even the perpetrators themselves are school residents. Cases of violence include emotional violence, verbal violence, physical violence, and sexual violence. Child-Friendly Schools are set up in an effort to reduce cases of child abuse and as a form of state, a responsibility to fulfill the rights of children as mandated in law no. 35 of 2014. In an effort to realize the Child-Friendly School on an ongoing and better basis, the community service team socialized the strategy and policy of child-friendly schools for PGSD students of Mataram University. PGSD students are chosen because they are prospective teachers who will definitely jump into the school. The socialization was held on 12 August 2020 through the Zoom Meeting.Socialization participants are given information related to six indicators to measure the achievement of SRA, namely: (1) SRA policy, (2) curriculum implementation, (3) education and education personnel trained in children's rights, (4) facilities and infrastructure of SRA, (5) child participation and (6) participation of parents, community institutions, business world, stakeholders and alumni. The outside target or achievement of this socialization activity is improvement the understanding of students regarding child-friendly school policies and strategies.Keywords: socialization; violence; sra policy